Uncovering the central role of GhSPL13 in vegetative growth, root architecture, and stress responses in cotton - Sahar Sadaqat; Muhammad Awais; Muhammad Saad bin Tahir; Ramsha Ajmal; Aneela Yasmeen; Saira Azam; Naila Shahid; Ayesha Latif; Allah Bakhsh; Ruhangiz Mammadova; Abdul Qayyum Rao (Plant Science, 2026)

Comparative study on the implementation of Custom Convolutional Neural Networks (CNNs), MobileNet V3 and ResNet-50 architecture for defect detection in Carbon Fiber Reinforced Plastics (CFRPs) - Hussnain Abid; Muhammad Daniyal Hassan; Saad Nauman (Next Research, 2026)

Multilevel determinants of health-promoting behaviors in populations: An integrative synthesis of behavioral dynamics, socio-cultural structures, and policy-level drivers of public health outcomes - Jenny Wilson; Muhammad Essa; Asra Mehar; Kiran Kumar; Ali Saad R. Alsubaie (Next Research, 2026)

Adaptive strategies of Tamarix aphylla in hyper-saline conditions of Cholistan Desert - Muhammad Akram; Nargis Naz; Hafiz Muhammad Mohsin Hassan; Maqbool Ahmed; Leman Aliyeva; Muhammad Yousaf Nadeem; Hind Saad Alsubaie; Sahar Anwar Almalki; Abdelrahman R. Ahmed; Abdullah R. Alanzi (The Science of Nature, 2026)

Molecular target for neuroinflammation and pain management: transient receptor potential vanilloid 1 - Zunera Chauhdary; Muhammad Saad Masood; Muhammad Irfan; Amina Shafi; Duryab Rafique; Abeesha Arif; Maryam Akmal (Inflammopharmacology, 2026)

Yucca filamentosa extract therapeutic potential against neuro-inflammation and demyelination through modulation of eicosanoids - Malik Saad Ullah; Areej Asghar; Zunera Chauhdary; Muhammad Irfan; Samina Afzal (Inflammopharmacology, 2026)

Contamination levels, eco-health risks, and source identification of some potentially toxic elements in roadside dust along the Indus Highway (N-55), Pakistan using compositional data analysis - Amanullah; Wajid Ali; Saad Khan; Said Muhammad; Abdur Raziq; Muhamamd Nafees; Imran Ud Din (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Building Information Modelling (BIM) adoption in developing economies: an analysis of barriers, critical success factors, and a public infrastructure viability framework - Qaim Shah; Syed Saad; Muhammad Hasnain; Waseem Khan; Ijaz Ahmad; Abdul Haq (Innovative Infrastructure Solutions, 2026)

A comprehensive review of innovative green hydrogen production technologies and catalysis developments - Saad Uddin Mahmud; Yew Heng Teoh; Heoy Geok How; Haseeb Yaqoob; Mohamad Yusof Idroas; Thanh Danh Le; Muhammad Ahmad Jamil; Hafiz Muhammad Ali; Muhammad Wakil Shahzad (Journal of Environmental Management, 2026)

Retraction notice to “Does communicable diseases (including COVID-19) may increase global poverty risk? A cloud on the horizon” [Environ. Res. 187 (2020) 109668] - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Saad M. Alotaibi; Muhammad Moinuddin Qazi Abro; Xuan Vinh Vo; Khalid Zaman (Environmental Research, 2026)

Integrated terrain analysis and SWAT-based modeling for assessing hydrological dynamics of the Upper Jhelum River Basin, Pakistan - Samavia Shahid; Muhammad Nasar-u-Minallah; Muhammad Saad; Muhammad Waqar; Mohamed Hassan Fathima Nuskiya (Acta Geophysica, 2026)

Toward next-generation PEM fuel cells: Recent progress in materials, design, and commercialization - Hongsheng Xu; Akeel Qadir; Xiangyu Zeng; Saad Ahmed; Muhammad Hassan (Journal of Environmental Chemical Engineering, 2026)

RETRACTED ARTICLE: Modification of a nonlinear transfer-function noise model for the estimation of groundwater recharge - Saad Zaheer; Muhammad Atiq Ur Rehman Tariq; Abdullah Nadeem (Hydrogeology Journal, 2026)

First report of Steneotarsonemus spinki Smiley (Trombidiformes: Tarsonemidae) infesting greenhouse-grown rice (Oryza sativa L. ssp. indica cv. MR 297) in Malaysia - Noriha Mat Amin; Munirah Tharek; Suhana Yusof; Amin Asyraf Tamizi; Maisarah Mohamad Saad; Siti Akhtar Mohshim; Azlinda Erny Yunus; Muhammad Zamharir Ahmad (Australasian Plant Pathology, 2026)

Therapeutic impact of SGLT2 inhibitors following transcatheter aortic valve implantation: a grade-assessed systematic review and meta-analysis. - Khadeeja Ali Hamzah; Yousif Hameed Kurmasha; Ali Saad Al-Shammari; Mohammedsadeq A. shweliya; Ali Alsajad Hussein Al-Janabi; Muhammad Shahzaib; Atef akoum; Yasar Sattar (European Journal of Clinical Pharmacology, 2026)

Data-driven explainable artificial intelligence models for predicting CO2 uptake in metal–organic frameworks - Mohd Azfar Shaida; Laiba Saleem; Syed Ali Waqas Ahmad; Saad Shamim Ansari; Syed Muhammad Ibrahim (Environmental Science and Pollution Research, 2026)

Insights into performance degradation of roof runoff treatment in field-scale bioretention facilities packed with zeolite and volcanic rock over three years of continuous operation - Jiakai Hu; Ronghua Xu; Jingyi Jiang; Muhammad Rizwan; Mohd Fadhil Md Din; Elsayed Ali Elsayed Ali; Eli Hendrik Sanjaya; AbdelGawad Saad; Zhe Kong; Hong Chen (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “global research on the air quality status in response to the electrification of vehicles” [Science of the Total Environment, 795, (2021), 148861] - Yansong Bao; Khalid Mehmood; Saifullah; Muhammad Yaseen; Saad Dahlawi; Muhammad Mohsin Abrar; Shah Fahad (Science of The Total Environment, 2026)

Evaluating the Accuracy of Machine Learning Models with Short-Term Lag Inputs for Univariate Daily Streamflow time Series Forecasting - Saad Ashfaq; Safia Waseem; Muhammad Tufail; Aqil Tariq (Water Resources Management, 2026)

A comparative analysis of tsunami flow through emergent and submerged coastal vegetation using numerical simulation - Syed Muhammad Ahmad Bukhari; Naveed Anjum; Saad Abbas; Adnan Shahid; Abdul Basit Bukhari; Ghufran Ahmed Pasha (Natural Hazards, 2026)

Impact of CuS Nanoparticles on Morpho-Biochemical Traits and Yield in Two Oilseed Crops; Eruca Sativa and Linum Usitatissimum - Jehangir Khan; Mah Rukh; Saad Hanif; Muhammad Zia (Journal of Soil Science and Plant Nutrition, 2026)

Genomic characterization of Burkholderia glumae K6 and B. gladioli UPMBG7: causal agents of bacterial panicle blight in Malaysia - Adam Zafdri Md Zali; Siti Izera Ismail; Norsazilawati Saad; Muhammad Asyraf Md Hatta; Mohd Razi Ismail; Mohd Termizi Yusof; Mansor Hakiman; Syari Jamian; Sumaiyah Abdullah; Dzarifah Zulperi (European Journal of Plant Pathology, 2026)
Bacterial panicle blight (BPB), caused by Burkholderia glumae and B. gladioli , is a major threat to rice in Malaysia, with potential yield losses up to 75%. In June 2021, BPB symptoms were detected in Kedah rice fields. Isolates were identified through phenotypic traits, pathogenicity tests, and molecular analysis (16S rRNA and gyrB sequencing). Whole-genome sequencing of B. glumae K6 and B. gladioli UPMBG7 was performed using the Illumina NovaSeq 6000 platform. The assembled draft genome of B. glumae K6 contained 210 contigs, with a total genome size of 6.57 Mbp, 68.33% G + C content, and 5,641 coding sequences (CDS). It harbored toxoflavin biosynthesis genes ( toxABCDE , toxJ ) and a Type III secretion system (T3SS), contributing to its pathogenicity. B. gladioli UPMBG7 contained 124 contigs, with a total genome size of 8.22 Mbp, G + C content of 67.99, and 7,022 coding proteins. B. gladioli lacked the toxI gene for toxoflavin production but compensated with pyoverdine siderophore genes ( pvdA ), which facilitate iron acquisition. These findings highlight divergent infection mechanisms, with B. glumae relying on toxoflavin-mediated virulence and B. gladioli on resource competition. The genomic insights support the development of resistant rice cultivars, biological controls, and molecular diagnostics to improve BPB management in Malaysia.

Correction: Hormetic Priming of Sorghum Water Extract Imparts Drought Tolerance and Mediated Antioxidative Defense in Wheat - Muhammad Usman Ibrahim; Abdul Khaliq; Basmah M. Alharbi; Shehnaz kousar; Hayam A. Alwabsi; A. Altalhi; Abdulrahman Saad Aldawood; Khawaja Ghulam Rasool (Agricultural Research, 2026)

Hormetic Priming of Sorghum Water Extract Imparts Drought Tolerance and Mediated Antioxidative Defense in Wheat - Muhammad Usman Ibrahim; Abdul Khaliq; Basmah M. Alharbi; Shehnaz kousar; Hayam A. Alwabsi; A. Altalhi; Abdulrahman Saad Aldawood; Khawaja Ghulam Rasool (Agricultural Research, 2026)

Adaptive morphological and physiological strategies of Sporobolus ioclados in desert ecosystem - Muhammad Akram; Nargis Naz; Ummar Iqbal; Syeda Refat Sultana; Fahim Arshad; Muhammad Waheed; Muhammad Adeel Ghafar; Hafiz Muhammad Mohsin Hassan; Arslan Asghar; Abeer Hashem; Dalal Saad Alharbi; Graciela Dolores Avila-Quezada; et al. (The Science of Nature, 2026)

A Snapshot of Brucellosis as an Occupational Health Hazard in Animal Handlers of an Agroecological Zone of Southern Punjab, Pakistan - Abdul Sammad Ali Khan Shirwany; Mian Muhammad Awais; Saad Masood; Aayesha Riaz; Masood Akhtar; Hosny El-Adawy; Faqir Muhammad; Muhammad Irfan Anwar; Mamoona Chaudhry (Journal of Agromedicine, 2026)

Engineered microbial consortium enhances tomato salt tolerance through rhizosphere modulation for sustainable crop production - Linlin Sun; Xinyu Jia; Xiaohu Zhou; Junsong Yue; Zihe Deng; Muhammad Saad Ahmed; Xiaochen Liu; Zhansheng Wu (Journal of Cleaner Production, 2026)

A review on CO2 mineralization in saline aquifers: Advances, challenges, and future prospects for sustainable carbon sequestration - Arshad Khan; Fahad Khan; Tatenda Raphinos Marapira; Saad Alafnan; Arshad Raza; Mohamed Mahmoud; Muhammad Shahzad Kamal (Journal of Environmental Management, 2026)

Explainable deep learning combined attention-based LSTM for building energy prediction: a framework from the perspective of supply side - Muhammad Saad Ul Haq; Wenjie Ji; Xingyu Pei; Shuli Liu; Yang Geng; Borong Lin; Haider Ali (Energy and Buildings, 2026)

Stability of performance in a hierarchical system during isometric force production and effects of visual feedback - Sayan Deep De; Xiaogang Hu; Muhammad Saad Khan; Mark L. Latash (Experimental Brain Research, 2026)
We address the underexplored role of visual feedback in ensuring stability of pressing force produced in isometric conditions by the two hands. We considered the task as a two-level hierarchy (total force, F TOT , and hand forces, F HAND ) and used the framework of the uncontrolled manifold hypothesis to quantify synergies stabilizing F TOT and F HAND . Young healthy persons performed steady-state forces with visual feedback and targets for the forces produced by each hand and/or for the total force. We quantified inter-trial and within-a-trial (across time windows) variance components affecting and not affecting F TOT and F HAND . Variables with visual feedback, F TOT or F HAND , showed force-stabilizing synergies reflected in the structure of variance, while variables without visual feedback failed to show such synergies. The synergies were consistently stronger when the feedback was continuous, compared to when the feedback disappeared when the cursor was inside the target. The results showed a strong dependence between variance that did not affect F TOT (within the corresponding solution space) and variance that affected each F HAND across the feedback conditions. Within-a-trial synergy indices were significantly lower than those in the inter-trial analysis. The data are interpreted as reflecting hierarchical control with synergies at both levels of the hierarchy, those that define F TOT and F HAND . These synergies get contributions from inter-trial force sharing variability and sensory feedback-based covariation of forces produced by the elements (fingers or hands) along individual trials. Combining inter-trial and within-a-trial analysis of variance may provide an important toolbox to explore cases of impaired control of action stability.

Morphological, Biochemical, Yield, and Metal Accumulation Response of Eruca sativa (L.) and Linum usitatissimum (L.) by MnS NPs Application - Jehangir Khan; Mah Rukh; Saad Hanif; Amina Afzal; Muhammad Zia (Journal of Plant Growth Regulation, 2025)

Ameliorative effects of Ocimum sanctum in Oreochromis niloticus against waterborne sub-lethal cadmium toxicity - Muhammad Attaullah Saad; Syed Makhdoom Hussain; Shafaqat Ali; Abdul Ghafoor; Syed Zakir Hussain Shah; Abdulrahman Alasmari; Anam Khalid (Veterinary Research Communications, 2025)

Halotolerant Bacillus Aryabhattai Strain PM34 Mitigates Salinity Stress and Enhances the Physiology and Growth of Maize - Muhammad Atif Azeem; Salman Khan; Fawad Ali; Sajjad Ahmad; Gul Rahim; Muhammad Iftikhar; Majid Iqbal; Rawa Saad Aljaloud; Khaloud Mohammed Alarjani; Hassan Javed Chaudhary (Journal of Plant Growth Regulation, 2025)

Consortium of Endophytic Bacillus australimaris CK11 and Staphylococcus epidermidis CK9 from Commiphora gileadensis Mediates Tomato Resilience to Combined Salinity, Heat, and Drought Stresses - Syed Saad Jan; Nasir Ali Khan; Sajjad Asaf; Raheem Shahzad; Lubna; Muhammad Imran; Saqib Bilal; In-Jung Lee; Ahmed Al-Harrasi (Journal of Plant Growth Regulation, 2025)

Molecular Epidemiology and Resistant Gene Mapping of Bacterial Isolates from Houbara bustards - Maham Fatima; Tasleem Kausar; Amjad Islam Aqib; Muhammad Shoaib; Farid S. Ataya; Mohamed Saad Daoud (Current Microbiology, 2025)

Ex-situ multi-media bioleaching and functional characterization of indigenous fungal strains for chromium and zinc remediation in polluted soils - Ibrar Khan; Muhammad Bilal Akram; Aneela Rehman; Mujaddad Ur Rehman; Tawaf Ali Shah; Saad A. Alamri; Yasser S. Mostafa; Abdulrahman A. Almehizia (Biodegradation, 2025)

YOLOv5 Revisited: A Lightweight yet Accurate Framework for Plant Disease Detection in Agricultural Applications - Huria Ali; Muhammad Imran; Saad Irfan Khan; Anees Tariq; Hassan Dawood; Hussain Dawood (Applied Fruit Science, 2025)

Predicting microplastic accumulation zones and shoreline changes along the Kelantan coast, Malaysia, using integrated GIS and ANN models - Muhammad Zakwan Anas Abd Wahid; Anis Syuhada Saufi; Nurul Aliah Farhana Kamarulzaman; Mohamed Syazwan Osman; Mohamad Sufian So'aib; Samsul Setumin; Adi Izhar Che Ani; Fathinul Najib Ahmad Saad (Marine Pollution Bulletin, 2025)

Quinic acid and its derivatives protect against phytohaemagglutinin-induced Alzheimer's-like neurotoxicity in SH-SY5Y cells by down-regulating p38 MAPK signaling pathway - Kinza Rafi; Shaheen Faizi; Syed Saad Hussain; Shumaila Shamshad; Muhammad Ali Versiani; Shabana U. Simjee (Toxicology and Applied Pharmacology, 2025)

A hybrid 3D CNN-LSTM model with soft spatial attention mechanism for accurate hyperspectral image classification - Mohamed Sultan Mohamed Ali; Md Sakib Bin Islam; Molla E. Majid; Saad Bin Abul Kashem; Amith Khandakar; Muhammad E.H. Chowdhury (Remote Sensing Applications: Society and Environment, 2025)

Influence of cationic, anionic, and non-ionic surfactants on in-situ growth of polyaniline on alumina ceramic membranes for the effective crude oil-in-water emulsion separation: Experimental and machine learning approaches - Muhammad Saad Khan; Umair Baig; Abdul Waheed; Sohaib Abdelazem; Isam H. Aljundi (Desalination, 2025)

Accelerated CO2 dissolution and mineralization in saline aquifers using alkaline earth metals - Tatenda Marapira; Saad Alafnan; Arshad Raza; Mohamed Mahmoud; Mobeen Murtaza; Muhammad Shahzad Kamal (Chemical Engineering Journal, 2025)

Submergence stress in plants: molecular mechanisms, physiological changes, and adaptive responses - Noreen Iftikhar; Muhammad Saad Bhutta; Narmeen Tariq Zaman; Ayesha Khalid; Ayesha Latif; Saira Azam; Naila Shahid; Aneela Yasmeen; Abdul Qayyum Rao (Physiology and Molecular Biology of Plants, 2025)

Exploring nonstructural NS5B protein to design a multi-epitope-based vaccine against HCV: immuno-informatics approach - Nouman Ali; Adeeba Ali; Muhammad Sheraz Yousuf; Arsheen Rehman; Saad Muhammad Islam; Bilal Ilyas; Aamir Ali (In Silico Pharmacology, 2025)

Offshore wind resource assessment and 7E analysis of offshore wind farms on the coastal belt of Pakistan - Talha Bin Nadeem; Asad A. Naqvi; Muhammad Saad; Kinza Malik; Ahsan Ahmed (Process Safety and Environmental Protection, 2025)

Oral adjuvanted Vibrio vaccine enhances antibody production and lysozyme activity in the serum and mucus of marine-cultured red hybrid tilapia (Oreochromis sp.) against V. harveyi and V. alginolyticus - Tilusha Manchanayake; Aslah Mohamad; Zahaludin Amir-Danial; Nadirah Abu Nor; Chin Yong-Kit; Muhammad Farhan Nazarudin; Roslindawani Md Nor; Qistina Hasnan; Mohd Zamri-Saad; Mohammad Noor Azmai Amal; Md Yasin Ina-Salwany; Annas Salleh (Fish & Shellfish Immunology, 2025)

Efficacy and Safety of Mesenchymal Stromal Cells for Steroid-Refractory Acute Graft-versus-Host Disease: An Updated Meta-Analysis of Randomized Controlled Trials - Iftikhar Khan; Umama Rehman; Fatima Aslam; Saad Khan; Umna Bhatti; Hussain Ramzan; Fatima Naveed; Javeria Nawaz; Syeda Malaika Raza; Kiran Inam; Faiza Rajput; Syed Muhammad Seyab; et al. (Stem Cell Reviews and Reports, 2025)

Ter-polymeric Cytocompatible Hydrogels Based on Sodium Alginate with Pectin and Acrylic Acid for Controlled Loxoprofen Sodium Oral Delivery; In vitro and In vivo Evaluation - Samiullah Khan; Abdur Rehman; Syed Faisal Badshah; Muhammad Saad (Journal of Pharmaceutical Innovation, 2025)

Polybenzimidazole-1D interconnected carbon framework decorated with nickel manganese oxide nanoparticles for hybrid supercapacitors - Muhammad Shahid Khan; Hong Meng; Ahmed Shuja; Hasan Ali; Hassan Tariq; Rehan Ullah; Abdullah Saad Alsubaie; Mohd Zahid Ansari; Yaqoob Khan; Imran Murtaza (Chemical Engineering Journal, 2025)

Flood susceptibility assessment and mapping using GIS-based analytical hierarchy process and frequency ratio models - Saad Ashfaq; Muhammad Tufail; Asif Niaz; Sher Muhammad; Hassan Alzahrani; Aqil Tariq (Global and Planetary Change, 2025)

Effect of sakuranetin against cyclophosphamide-induced immunodeficiency mice: role of IFN-γ/TNF-α/IgG/IgM/interleukins - Khalid Saad Alharbi; Sattam Khulaif Alenezi; Tariq Alsahli; Muhammad Afzal; Mohammad Jaffar Sadiq Mantargi; Imran Kazmi; Nadeem Sayyed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Numerical study on the balance of energy of a floating oscillating water column wave energy converter and breakwater hybrid system - Giri Ram; Mohd Rashdan Saad; Mohd Azzeri Md Naiem; Noh Zainal Abidin; Yasutaka Imai; Muhammad Zahir Ramli; Mohd Rosdzimin Abdul Rahman (Ocean & Coastal Management, 2025)

Selective Ion Separation via Capacitive Deionization: Current Practices and Future Directions - Hameer Chand; Mohamed Saad Gaballah; Muhammad Irtaza Sajjad Haider; Yangmin Ren; Hongjie Guo; Shuai Wang; Jiahui Ding; He Yang; Chuanjian Cui; Changyong Zhang (Chemical Engineering Journal, 2025)

Integrated landslide risk assessment utilizing open source satellite and ground data in the Himalayas of Northern Pakistan - Naseem Ahmad; Muhammad Shafique; Mian Luqman Hussain; Munawar Shah; Punyawi Jamjareegulgarn; Nassir Saad Alarifi; Mostafa R. Abukhadra (Natural Hazards, 2025)

Nanoparticle innovations in targeted cancer therapy: advancements in antibody–drug conjugates - Muhammad Sami Abdelhamid; Al-Hassan Soliman Wadan; Hager Adel Saad; Walaa A. El-Dakroury; Ahmed W. Hageen; Deyaa H. Mohammed; Sohaila Mourad; Osama A. Mohammed; Mustafa Ahmed Abdel-Reheim; Ahmed S. Doghish (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Constructing storm hydrographs at ungaged locations in a low-gradient watershed using SWAT calibrated to the NWM - Muhammad Izhar Shah; Emad H. Habib; Haitham A. Saad; Robert L. Miller (Hydrological Sciences Journal, 2025)

Boosted proton conduction in LAO electrolyte through Li segregation for High-Performance ceramic fuel cells - Nabeela Akbar; Muhammad Yousaf; M.A.K. Yousaf Shah; Jahangeer Ahmed; Asma Noor; Quazi Arif Islam; Yan Wu; Saad M. Alshehri; Naveed Mushtaq; Bin Zhu; Sara Paydar (Fuel, 2025)

Assessing access to safe drinking water in flood-affected areas of District Nowshera, Pakistan: A case study towards achieving sustainable development goal 6.1 - Muhammad Tufail; Muhammad Jamal Nasir; Aqil Tariq; Zahid Ali; Saad S. Alarifi (Ecohydrology & Hydrobiology, 2025)

Tissue-specific inhibition of brassinosteroids regulates panicle branching and grain yield in rice - Faisal Islam; Muhammad Saad Shoaib Khan; Xiaoyu Guo; Daowen Wang; Guang Qi (Science China Life Sciences, 2025)

Effect of soil types and moisture contents on the pupation behavior and adult emergence of Oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) - Muhammad Bilal; Muhammad Mamoon-ur-Rashid; Shabana Wazir; Muhammad Naeem; Asif Ishaq; Rana Muhammad Kaleem Ullah; Abdulrahman Saad Aldawood (International Journal of Tropical Insect Science, 2025)

Selective lead ion sensing via cotton pad-based Na2EDTA capped AuNPs: A smartphone-assisted colorimetric method - Evana Sultana; Md Zewel Rana; Muhammad Shamim Al Mamun; Mohamed Aly Saad Aly; Ghada E. Khedr; Jamil Ahmed; Waleed Alahmad (Chemosphere, 2025)

Correction: Polychlorinated biphenyls induced toxicities upon cell lines and stem cells: a review - Muhammad Zaffar Hashmi; Anaela Shoukat; Siwatt Pongpiachan; Yasar N. Kavil; Saeed Saad Alelyani; Mohammed M. Alkasbi; Mohamed Hussien; Md Toushik Ahmed Niloy (Environmental Geochemistry and Health, 2025)

The efficacy of egg albumin nanoparticles adjuvanted Clostridium perfringens type D toxoid vaccine in rabbits - Mehwish Saeed; Saad Zafar; Zarreen Sajjad; Rizwan Aslam; Sultan Ali; Muhammad Shahid Mahmood; Mueed Aayan; Maria Sophy; Saqib Umer; Sajjad Ur Rahman; Muhammad Naveed Anwar (Brazilian Journal of Microbiology, 2025)

ECCDN-Net: A deep learning-based technique for efficient organic and recyclable waste classification - Md. Sakib Bin Islam; Md. Shaheenur Islam Sumon; Molla E. Majid; Saad Bin Abul Kashem; Mohammad Nashbat; Azad Ashraf; Amith Khandakar; Ali K. Ansaruddin Kunju; Mazhar Hasan-Zia; Muhammad E.H. Chowdhury (Waste Management, 2025)

Exploring the role of Bisphenol A in obesity-driven colorectal cancer progression: network toxicology and multi-organ pathology in animal models - Muhamad Fikri Shazlan Saad; Muhammad Nazrul Hakim Abdullah; Vuanghao Lim; Hasnah Bahari; Boon Yin Khoo; Jun Jie Tan; Yoke Keong Yong (Toxicology and Applied Pharmacology, 2025)

A global review on perfluoroalkyl acids (PFAAs) in the riverine systems: Environmental behaviours and risks implications - Muhammad Younas; Kifayatullah Khan; Maria Zeb; Muhammad Yaseen; Noor Samad Shah; Hassan Alshemmari; Yasar N. Kavil; Saeed Saad Alelyani; Mohamed Hussien; Sidra Zeb; Di Du (Science of The Total Environment, 2025)

Comprehensive analysis of leak impacts on liquid-gas multiphase flow using statistical, wavelet transform, and machine learning approaches - Hicham Ferroudji; Muhammad Saad Khan; Abinash Barooah; Wahib A. Al-Ammari; Ibrahim Hassan; Rashid Hassan; Ahmad K. Sleiti; Sina Rezaei Gomari; Matthew Hamilton; Mohammad Azizur Rahman (Process Safety and Environmental Protection, 2025)

Photovoltaic module efficiency enhancement system by novel cooling techniques: Effect of phase change material and fins - Saad Saeed; Abid Hussain; Imran Ali; Hanzla Shahid; Muhammad Anwar; Hafiz Muhammad Ali (Process Safety and Environmental Protection, 2025)

Biomitigation of noxious metal ions using engineered lignin-based nanocomposites for sustainable environment - Zaeem Bin Babar; Rashid Iftikhar; Komal Rizwan; Shahid Munir; Mashhood Urfi; Fawad Ashraf; Muhammad Ali Inam; Shahid Iqbal; Muhammad Saad; Sajid Mahmood; Nasser S. Awwad; Hala A. Ibrahium (Journal of Water Process Engineering, 2025)

Corrigendum to ‘Trace element bioaccumulation in edible red seaweeds (Rhodophyta): A risk assessment for consumers’ [Environ. Pollut. 307 (2022) 1–10/119560] - Md Solaiman Hossain; Eurida Liyana; Saad Al-din Sifat; Fuad Ameen; Md Akram Ullah; Yeasmin Nahar Jolly; Shamshad Begum Quraishi; Mofazzal Hossain; Sazlina Salleh; Sharmin Akter; Mohammad Afzal Hossain; Muhammad Zobayer Bin Mukhlish; et al. (Environmental Pollution, 2025)

Reshaping the healthcare world by AI-integrated wearable sensors following COVID-19 - Bangul Khan; Rana Talha Khalid; Khair Ul Wara; Muhammad Hasan Masrur; Samiullah Khan; Wasim Ullah Khan; Umay Amara; Saad Abdullah (Chemical Engineering Journal, 2025)

Evaluating the safety and effectiveness of tolvaptan in patients with heart failure and renal impairment: a systematic review and meta-analysis - Aashish Kumar; Umer Iqbal; Shafin Bin Amin; Syed Ali Arsal; Syed Muhammad Sinaan Ali; Muhammad Ashir Shafique; Muhammad Saad Shahid; Aimen Naz; Emediong Santhus Asuka (European Journal of Clinical Pharmacology, 2025)

Polychlorinated biphenyls induced toxicities upon cell lines and stem cells: a review - Muhammad Zaffar Hashmi; Anaela Shoukat; Siwatt Pongpiachan; Yasar N. Kavil; Saeed Saad Alelyani; Mohammed M. Alkasbi; Mohamed Hussien; Md Toushik Ahmed Niloy (Environmental Geochemistry and Health, 2025)

Synergistic anticancer effects of interleukin-21 combined with therapeutic peptides in multiple cancer cells - Muhammad Akram; Nao Akusa Fujimura; Saad Tahir; Rabia Abbas; Mohsin Ahmad Khan; Kausar Malik; Nadeem Ahmed (Biotechnology Letters, 2025)

A novel (−)-(2S)-7,4′-dihydroxyflavanone compound for treating age-related diabetes mellitus through immunoinformatics-guided activation of CISD3 - Abdur-Rehman Munir; Saad Ilyas Baig; Muhammad Asif Razzaq; Fatima Rauf; Yasir Ali; Syed Muhammad Abdullah Azam (Biogerontology, 2025)

Bio-catalytic activity of novel poly(ethylene glycol) methacrylate hybridized silver nanomaterials - Natasha Anwar; Mohib Shah; Saad Haroon Anwar; Muhammad Ishaq Ali Shah; Amir Zada; Hammad Ahmad Jan; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah (South African Journal of Botany, 2025)

Prediction of CO2 uptake in bio-waste based porous carbons using model agnostic explainable artificial intelligence - Mohd Azfar Shaida; Saad Shamim Ansari; Raeesh Muhammad; Syed Muhammad Ibrahim; Izharul Haq Farooqi; Abdulkarem Amhamed (Fuel, 2025)

QUAL2K water quality model: A comprehensive review of its applications, and limitations - Siti Salwa Mohamad Noor; Noor Aida Saad; Muhammad Fitri Mohd Akhir; Muhamad Syafiq Abd Rahim (Environmental Modelling & Software, 2025)

Utilizing contemporary machine learning techniques for determining soilcrete properties - Waleed Bin Inqiad; Muhammad Saud Khan; Zohaib Mehmood; Naseer Muhammad Khan; Muhammad Bilal; Mohammed Sazid; Saad S. Alarifi (Earth Science Informatics, 2025)
Soilcrete is an innovative construction material made by combining naturally occurring earth materials with cement. It can be effectively used in areas where other construction materials are not readily available due to financial or environmental reasons since soilcrete is made from readily available natural clay. It can also help to cut down the greenhouse gas emissions from the construction industry by encouraging the use of resources that are locally available. Thus, it is imperative to reliably predict different properties of soilcrete since the accurate determination of these properties is crucial for the widespread use of soilcrete materials. However, the laboratory determination of these properties is subjected to significant time and resource constraints. As a result, this research was undertaken to provide empirical prediction models for the density, shrinkage, and strain of soilcrete mixes using two machine learning algorithms: Gene Expression Programming (GEP) and Extreme Gradient Boosting (XGB). The analysis revealed that XGB-based predictions correlated more with real-life values than GEP having training $${\text{R}}^{2}=0.999$$ R 2 = 0.999 for both density and shrinkage prediction and $${\text{R}}^{2}=0.944$$ R 2 = 0.944 for strain prediction. Moreover, several explanatory analyses including individual conditional expectation (ICE) analysis and shapely analysis were done on the XGB model which showed that water-to-binder ratio, metakaolin content, and modulus of elasticity are some of the most important variables for forecasting soilcrete materials properties. Furthermore, an interactive graphical user interface (GUI) has been developed for effective utilization in civil engineering industry to forecast these properties of soilcrete materials.

Assessing the Effectiveness of Audio-Visual vs. Visual Neurofeedback for Attention Enhancement: A Pilot Study with Neurological, Behavioural, and Neuropsychological Measures - Osama Ejaz; Muhammad Abul Hasan; Faryal Raees; Maham Hammad; Saad Ahmed Qazi (Brain Topography, 2025)

Adaptive mechanisms of wheat cultivars to lead toxicity through enhanced oxidative defense, ionomic redistribution, and anatomical modifications - Muhammad Anas; Muhammad Saad Bashir; Khadija Saleem; Atika Noor; Umar Masood Quraishi (Journal of Plant Physiology, 2024)

Triangular relation of food processing, nutrition, and osteoarthritis: A solution for the management and prevention of osteoarthritis? - Arashi Shahid; Ammar B. Altemimi; Iahtisham -Ul-Haq; Muhammad Inam-ur-Raheem; Roshina Rabail; Muhammad Hamdan Rashid; Sadia Kafeel; Muhammad Saad Akram; Amin Mousavi Khaneghah; Rana Muhammad Aadil (Food Bioscience, 2024)

Socio-economic benefits and policy implications of generating sustainable energy from municipal solid waste in Pakistan - Waqas Ahmad; Muhammad Hassan; Shah Fahad Bin Masud; Muhammad Saad Amjad; Fatin Samara; Zeshan; Mustafa Anwar; Muhammad Zeeshan Rafique; Tahir Nawaz (Energy and Climate Change, 2024)

Real-time expression and in silico characterization of pea genes involved in salt and water-deficit stress - Muhammad Farooq; Rafiq Ahmad; Muhammad Shahzad; Saad Ur Rehman; Yasar Sajjad; Amjad Hassan; Mohammad Maroof Shah; Amber Afroz; Sabaz Ali Khan (Molecular Biology Reports, 2024)

Alleviating Cadmium Toxicity in Eggplant (Solanum melongena L.) and Human Health Risk Analysis: Contrasting Effects of Gypsum, Farm Manure and Poultry Manure - Anees Irfan; Hamaad Raza Ahmad; Muhammad Tahir Shehzad; Fatima Siddiqa; Ada Ashban; Muhammad Saad Bin Zafar; Muhammad Hassan Bashir (Journal of Soil Science and Plant Nutrition, 2024)

Recombinant expression, downstream optimization, and therapeutic evaluation of recombinant human interleukin-37 for cancer therapy - Zaheer Abbas; Samia Afzal; Nao Akusa Fujimura; Muhammad Akram; Saad Tahir; Kausar Malik; Nadeem Ahmed (Biotechnology Letters, 2024)

Hypoxia stress: plant’s sensing, responses, and tolerance mechanisms - Farwa Basit; Muhammad Khalid; Ali El-Keblawy; Mohamed S. Sheteiwy; Saad Sulieman; Izabela Josko; Faisal Zulfiqar (Environmental Science and Pollution Research, 2024)

Reorientation of energy policy and management: Integrated Energy Planning (IEP) framework implementation for Renewable and Thermal Energy Systems (RTES) - Humera Tubussum; Muhammad Aslam; Hezlina Mohd Hashim; Maran Marimuthu; K.H. Mahmoud; Abdullah Saad Alsubaie; Abdul Waheed Bhutto; Aqeel Ahmed Bazmi; Awais Bokhari; Abdul-Sattar Nizami (Process Safety and Environmental Protection, 2024)

Copper stress in rice: Perception, signaling, bioremediation and future prospects - Md Mahfuzur Rob; Delara Akhter; Tariqul Islam; Debu Kumar Bhattacharjya; Muhammad Saad Shoaib Khan; Faisal Islam; Jian Chen (Journal of Plant Physiology, 2024)

Synergistic biochar and Serratia marcescens tackle toxic metal contamination: A multifaceted machine learning approach - Hamid Rehman; Aqib Hassan Ali Khan; Tayyab Ashfaq Butt; Muhammad Toqeer; Muhammad Bilal; Mahtab Ahmad; Ahmed Abdullah Alawi Al-Naghi; Enamur Rahim Latifee; Omar Ali Saad Algassem; Mazhar Iqbal (Journal of Environmental Management, 2024)

Proximate composition and prevalence and exposure assessment of aflatoxins intake through consumption of fresh carrot and processed marketed carrot products in South Punjab, Pakistan - Aneela Nijabat; Shahwana Bibi; Maryam Ajmal; Saher Nawaz; Muhammad Zaheer Sajid; Saad Ullah Khan Leghari; Muhammad Mahmood-ur-Rehman; Naima Huma Naveed; Aamir Ali; Philipp W. Simon (Natural Product Research, 2024)

Detection of Mobile and Immobile Solute Transport and Their Residence Time in Saturated Low and High Permeability Soil Layers - Muhammad Zaheer; Ehsan Ul Haq; Ning Huang; Ahmed Amara Konaté; Ghulam Mujtaba Shah; Raja Umer Sajjad; Saad Ahmed Mashwani (Water, Air, & Soil Pollution, 2024)

Immunoinformatic-based drug design utilizing hesperetin to target CISD2 activation for liver aging in humans - Saad Ilyas Baig; Maria Naseer; Abdur-Rehman Munir; Yasir Ali; Muhammad Asif Razzaq (Biogerontology, 2024)

Prediction of surface urban heat island based on predicted consequences of urban sprawl using deep learning: A way forward for a sustainable environment - Shun Fu; Lufeng Wang; Umer Khalil; Ali Hassan Cheema; Israr Ullah; Bilal Aslam; Aqil Tariq; Muhammad Aslam; Saad S. Alarifi (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Optimization of strontium removal by Tetraselmis chui grown in bubble column photobioreactors - Inés Segovia-Campos; Montserrat Filella; Muhammad Saad Bin Zahid; Luísa Barreira; Karl Perron; Daniel Ariztegui (Algal Research, 2024)

Application of deep learning for livestock behaviour recognition: A systematic literature review - Ali Rohan; Muhammad Saad Rafaq; Md. Junayed Hasan; Furqan Asghar; Ali Kashif Bashir; Tania Dottorini (Computers and Electronics in Agriculture, 2024)

A review of heavy metals pollution in riverine sediment from various Asian and European countries: Distribution, sources, and environmental risk - Maria Zeb; Kifayatullah Khan; Muhammad Younas; Abida Farooqi; Xianghui Cao; Yasar N. Kavil; Saeed Saad Alelyani; Mohammed M. Alkasbi; Abdullah G. Al-Sehemi (Marine Pollution Bulletin, 2024)

Dynamic interplay of silica-coated iron oxide nanocomposite on soil-plant system to mitigate Cd toxicity in rice - Faisal Islam; Muhammad Saad Shoaib Khan; Sulaiman Ahmed; Aziz Ul Ikram; Fakhir Hannan; Mehmood Jan; Muhammad Sajid; Ali Ahmed Zaky Shoaib; Shan Liu; Jian Chen (Journal of Cleaner Production, 2024)

Mitigating potential of polystyrene microplastics on bioavailability, uptake, and toxicity of copper in maize (Zea mays L.) - Muhammad Saad Bashir; Umair Saeed; Jawad Aslam Khan; Muhammad Saeed; Ghazala Mustafa; Riffat Naseem Malik (Environmental Pollution, 2024)

Correction: Spatial distribution and health risks assessment of heavy metals in e-waste dumping sites from Pakistan - Muhammad Zaffar Hashmi; Sohaib Khan; Yasar N. Kavil; Saeed Saad Alelyani; Abdullah G. Al Sehemi; Ahmad Hasnain; Sidra Shakil; Shuhong Wang; Zulkifl Ahmed (Environmental Geochemistry and Health, 2024)

Surface modified ZnO NPs by betaine and proline build up tomato plants against drought stress and increase fruit nutritional quality - Saad Hanif; Snovia Farooq; Misbah Zeb Kiani; Muhammad Zia (Chemosphere, 2024)

Biochemical and nutritional analysis of seaweed (Iyengaria stellata) and its therapeutic significance, using antioxidant, antimicrobial, and hypoglycemic activities - Muhammad Imran; Arshad Iqbal; Arwa Abdulkreem AL-Huqail; Suliman Mohammed Suliman Alghanem; Syed Lal Badshah; Saad Alghamdi; Mazen Almehmadi; Uthman Balgith Algopishi; Baber Ali; Saima Sohni; Muhammad Ammar Javed; Doaa Bahaa Eldin Darwish (South African Journal of Botany, 2024)

Cenchrus ciliaris L. ameliorates cigarette-smoke induced acute lung injury by reducing inflammation and oxidative stress - Muhammad Irfan Aslam; Saad Touqeer; QurratUlAin Jamil; Muhammad Irfan Masood; Adeel Sarfraz; Shafaat Yar Khan; Muhammad Saeed Jan; Sulaiman Mohammed Abdullah Alnasser; Ashfaq Ahmad; Fatima Aslam; Shahid Muhammad Iqbal (South African Journal of Botany, 2024)

Spatial distribution and health risks assessment of heavy metals in e-waste dumping sites from Pakistan - Muhammad Zaffar Hashmi; Sohaib Khan; Yasar N. Kavil; Saeed Saad Alelyani; Abdullah G. Al Sehemi; Ahmad Hasnain; Sidra Shakil; Shuhong Wang; Zulkifl Ahmed (Environmental Geochemistry and Health, 2024)

Design and optimization of off-grid solar PV and biomass-based hybrid renewable energy system (HRES) for electrification of a rural community in Tharparkar, Pakistan - Talha Bin Nadeem; Ahsan Ahmed; Muhammad Saad; Asad A. Naqvi (Environment, Development and Sustainability, 2024)

Simple smartphone-based methods for the determination of bioactive compounds in wine - Kaja Kalinowska; Muhammad Saad Hussain; Gerjen Herman Tinnevelt; Marek Tobiszewski (Food Chemistry, 2024)

Comparative resistance of wheat genotypes to aphid infestation under varied sowing dates - Muhammad Nawaz; Irfanullah Khan; Farman Ullah Dawar; Ibni Amin Khalil; Zahid Hussain; Jan Saad; Syed Majid Rasheed; Khan Rahamdad (Ecological Genetics and Genomics, 2024)

Transcutaneous Delivery of Dexamethasone Sodium Phosphate Via Microneedle-Assisted Iontophoretic Enhancement – A Potential Therapeutic Option for Inflammatory Disorders - Muhammad Sohail Arshad; Saad Hussain; Saman Zafar; Sadia Jafar Rana; Tahir Ali Chohan; Muhammad Hamza; Kazem Nazari; Zeeshan Ahmad (Pharmaceutical Research, 2024)

Pakistan’s circular bio-economy: potential, opportunities and sustainable development - Yousaf Ali; Muhammad Sabir; Saad Afridi; Zahid Ullah (Environment, Development and Sustainability, 2024)

Hierarchical S-scheme heterojunction systems: A comprehensive review on outstanding photocatalysts - Huimin Han; Muhammad Raheel Khan; Irshad Ahmad; Ayman Al-Qattan; Ijaz Ali; Md Rezaul Karim; Hossein Bayahia; Farhat S. Khan; Zubair Ahmad; Saad Ullah (Journal of Water Process Engineering, 2024)

Smart and sustainable urban manufacturing for a circular economy - Muhammad Saad Amjad; Nancy Diaz-Elsayed (Environment, Development and Sustainability, 2024)

Efficient treatment of veterinary pharmaceutical industrial wastewater by catalytic ozonation process: degradation of enrofloxacin via molecular ozone reactions - Amir Ikhlaq; Zafar Masood; Umair Yaqub Qazi; Muhammad Raashid; Osama Shaheen Rizvi; Hafiz Abdul Aziz; Muhammad Saad; Fei Qi; Rahat Javaid (Environmental Science and Pollution Research, 2024)

GCDN-Net: Garbage classifier deep neural network for recyclable urban waste management - Md Mosarrof Hossen; Azad Ashraf; Mazhar Hasan; Molla E. Majid; Mohammad Nashbat; Saad Bin Abul Kashem; Ali K. Ansaruddin Kunju; Amith Khandakar; Sakib Mahmud; Muhammad E.H. Chowdhury (Waste Management, 2024)

Interactive mode of biochar-based silicon and iron nanoparticles mitigated Cd-toxicity in maize - Muhammad Umair Yasin; Fakhir Hannan; Raheel Munir; Sajid Muhammad; Muhammad Iqbal; Iqra Yasin; Muhammad Saad Shoaib Khan; Farah Kanwal; Yang Chunyan; Xingming Fan; Yinbo Gan (Science of The Total Environment, 2024)

Modified carbon paste electrode with choline proline in enhancing the performance of water electrolysis system for hydrogen production - Muhammad Usman; Fakrul Shahril Ezanie Zulkefli; Mohd Dzul Hakim Wirzal; Shafiq M. Hizam; Aliya Nurzafira Nor Zaidi; Muhammad Syaamil Saad (Fuel, 2024)

Underground hydrogen storage prospects in the Kingdom of Saudi Arabia - Arshad Raza; Mohamed Mahmoud; Muhammad Arif; Saad Alafnan (Fuel, 2024)

Barriers affecting implementation of life cycle cost analysis in construction projects: SEM approach - Muhammad Altaf; Wesam Salah Alaloul; Muhammad Ali Musarat; Sherif Mostafa; Rodney Stewart; Ali Hussain; Muhammad Babar Ali Rabbani; Syed Saad; Syed Ammad (Innovative Infrastructure Solutions, 2024)

Remediation of Cd-polluted soil, improving Brassica napus L. growth and soil health with Hardystonite synthesized with zeolite, limestone, and green Zinc oxide nanoparticles - Fakhir Hannan; Muhamamd Iqbal; Faisal Islam; Muhammamd A. Farooq; Muhammad Bilal Shakoor; Ahsan Ayyaz; Muhammad Saad Shoaib Khan; Juanjuan Li; Qian Huang; Weijun Zhou (Journal of Cleaner Production, 2024)

Comparative taxonomy and evolutionary significance of foliar epidermis in Jasminum L. (Oleaceae) based on light and scanning electron microscopy - Naeem Akhtar; Muhammad Q. Hayat; Umer Habib; Muhammad A. Khan; Saad I. Malik; Hina Hafeez; Adil Hussain; Azhar Hussain; Daniel Potter (Flora, 2024)

Exploring the hidden treasures of Nitella hyalina: a comprehensive study on its biological compounds, nutritional profile, and unveiling its antimicrobial, antioxidative, and hypoglycemic properties - Muhammad Imran; Arshad Iqbal; Syed Lal Badshah; Imtiaz Ahmad; Ashwag Shami; Baber Ali; Fatema Suliman Alatawi; Mohsen Suliman Alatawi; Yasser S. Mostafa; Saad A. Alamri; Ahlam A. Alalwiat; Majed A. Bajaber (World Journal of Microbiology and Biotechnology, 2023)

Engineering of Chlamydomonas reinhardtii chloroplast for mucosal immunotherapeutic against Newcastle disease virus - Sania Naeem; Naila Shahid; Mohsin Ahmad Khan; Saira Azam; Muhammad Saad Bhutta; Ayesha Latif; Aneela Yasmeen; Tahir Rehman Sami Ullah; Abdul Qayyum Rao; Kausar Malik (Journal of Applied Phycology, 2023)

Bibliometric analysis and literature review of occupant thermal comfort in naturally ventilated buildings (1995–2021) - Mohammed Awad Abuhussain; Badr Saad Alotaibi; Ikram Bello Suru; Yakubu Aminu Dodo; Mohammad Abdullah Alshenaifi; Muhammad Saidu Aliero (Environmental Science and Pollution Research, 2023)

Impacts of nutritive and bioactive compounds on cancer development and therapy - Sabira Sultana; Abdelhakim Bouyahya; Maksim Rebezov; Mohammad Ali Shariati; Abdelaali Balahbib; Aya Khouchlaa; Ouadie Mohamed El Yaagoubi; Adnan Khaliq; Nasreddine El Omari; Saad Bakrim; Gokhan Zengin; Muhammad Akram; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Proline coated ZnO NPs as nanofertilizer against drought stress: an in vitro study to Coriandrum sativum - Saad Hanif; Anila Sajjad; Muhammad Zia (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Synergistic effect of glycine betain-ZnO nanocomposite in vitro for the amelioration of drought stress in coriander - Saad Hanif; Anila Sajjad; Muhammad Zia (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Evaluation of possible attenuative role of chrysoeriol against polyethylene microplastics instigated testicular damage: A biochemical, spermatogenic and histological study - Muhammad Umar Ijaz; Faria Saher; Nemra Aslam; Ali Hamza; Haseeb Anwar; Saad Alkahtani; Hammad Ahmad Khan; Mian Nadeem Riaz (Food and Chemical Toxicology, 2023)

Redundant nerve roots indicate higher degree of stenosis in lumbar spine stenotic patients - Karim Rizwan Nathani; Muhammad Danish Barakzai; Hamid Hussain Rai; Komal Naeem; Fatima Mubarak; Haissan Iftikhar; Saad Akhtar Khan; Syed Ather Enam (Acta Neurologica Belgica, 2023)

Synthesis of ethyl levulinate over sulfonated lignin-based carbon catalyst as a fuel additive to biodiesel-diesel blends towards engine emissions - Abdull Hafidz Hassan; Muzakkir Mohammad Zainol; Muhammad Alif Samion; Muhammad A`qil Azlan; Mohd Asmadi; Ahmad Rafizan Mohamad Daud; Idris Saad; Nur Aina Najwa Mohd Nor Azman (Journal of Cleaner Production, 2023)

Lupeol, a plant triterpenoid mitigates salt induced stress: growth and antioxidative response of Brassica nigra under in vitro condition - Muhammad Zia; Joham Sarfraz Ali; Saad Hanif; Anila Sajjad; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Improved Transdermal Delivery of Rabies Vaccine using Iontophoresis Coupled Microneedle Approach - Muhammad Sohail Arshad; Saad Hussain; Saman Zafar; Sadia Jafar Rana; Nadia Ahmad; Najmusama Abdul Jalil; Zeeshan Ahmad (Pharmaceutical Research, 2023)

Trehalose: A Key Player in Plant Growth Regulation and Tolerance to Abiotic Stresses - Muhammad Umair Hassan; Muhammad Nawaz; Adnan Noor Shah; Ali Raza; Lorenzo Barbanti; Milan Skalicky; Mohamed Hashem; Marian Brestic; Saurabh Pandey; Saad Alamri; Yasser S. Mostafa; Ayman E. L. Sabagh; et al. (Journal of Plant Growth Regulation, 2023)

Enhanced soluble expression of active recombinant human interleukin-29 using champion pET SUMO system - Ayesha Munir; Nadeem Ahmed; Muhammad Akram; Nao Akusa Fujimura; Saad Tahir; Kausar Malik (Biotechnology Letters, 2023)

Aspen plus simulation model of municipal solid waste gasification of metropolitan city for syngas production - Muzaffar Mehdi; Syed Ali Ammar Taqvi; Asif Ahmed Shaikh; Saad Khan; Salman Raza Naqvi; Muhammad Shahbaz; Dagmar Juchelková (Fuel, 2023)

Application of UAV photogrammetry and electrical resistivity tomography for characterization of a complex landslide: a case study from northwest Himalayas, Pakistan - Syed Ahatsham Haider; Matloob Hussain; Aamir Ali; Muhammad Faheem Abbasi; Saad Wani (Natural Hazards, 2023)

Salt ion mediated changes in biochemical and anatomical characteristics of Brassica napus can be countered with Moringa Leaf extract - Noreen Akhter; Aqsa Noreen; Saima Saifullah; Ali Noman; Muhammad Muslim Shahnaz; Puleng M. Letuma; Abida Kausar; Maham Siddique; Mohamed Hashem; Saad Alamri; Omar Mahmoud Al-zoubi; Muhammad Saleem; et al. (South African Journal of Botany, 2023)

A Task Allocation Method for Multi-AUV Search and Rescue with Possible Target Area - Chang Cai; Jianfeng Chen; Muhammad Saad Ayub; Fen Liu (Journal of Marine Science and Engineering, 2023)
Task allocation is crucial for autonomous underwater vehicle (AUV) collaboration in multi-AUV maritime search and rescue missions. In real projects, there are possible target areas existing in task areas, which are not expected to be divided. Motivated by such a special situation, this paper proposes an area partitioning method to allocate the task to multiple AUVs and maintain the possible target area as a whole. First, the spatial structure of the task area is defined by the spiked Morse decomposition, which divides the task area according to a set of angles. Then, we perform a variational transformation to determine the optimal angles using the AUV order. Next, a customized backtracking method is introduced to determine the optimal AUV order which divides the task area among the multiple AUVs without disturbing the possible target areas. The proposed methodology is validated under various challenging scenarios using a different number of AUVs. The empirical results show that the divided possible target areas and workload variance were superior to the comparison methods. This indicates that the proposed method can generate stable solutions that effectively reduce the segmentation of possible target areas and keep the workload of the multiple AUVs balanced.

Architectural complexities and morphological variations of the indus fan and its elements: Understanding of the turbidite system through seismic characterization - Ehsan ul Haq; Ji Youliang; Hadayat Ullah; Khurram Shahzad; Nisar Ahmed; Saad Ahmed Mashwani; Muhammad Zaheer (Marine and Petroleum Geology, 2023)

Mapping smallholder plantation as a key to sustainable oil palm: A deep learning approach to high-resolution satellite imagery - Didit Okta Pribadi; Ernan Rustiadi; La Ode Syamsul Iman; Muhammad Nurdin; Supijatno; Asmadi Saad; Andrea Emma Pravitasari; Setyardi P. Mulya; Mia Ermyanyla (Applied Geography, 2023)

Modelling of geomorphological features of fluvial systems in Eromanga Basin and North Sea using 3D seismic attributes - Haris Ahmed Khan; Saifullah Abdul Qadir; Muhammad Jahangir Khan; Faraz Hasan Siddiqui; Mirza Saad Ahsan (Journal of Earth System Science, 2023)

A New Regional Drought Index under X-bar Chart Based Weighting Scheme – The Quality Boosted Regional Drought Index (QBRDI) - Zulfiqar Ali; Sadia Qamar; Nasrulla Khan; Muhammad Faisal; Saad Sh. Sammen (Water Resources Management, 2023)

Corrigendum to ‘Prediction of carbon-dioxide activity coefficient for solubility in ionic liquids using multi-non-linear regression analysis’, Chemosphere, 311, (2023), 1–10, 137102 - Sami-ullah Rather; Azmi M. Shariff; Aliyu Adebayo Sulaimon; Hisham S. Bamufleh; Ali Qasim; Muhammad Saad Khan; Hesham Alhumade; Usman Saeed; Walid M. Alalayah (Chemosphere, 2023)

A prediction model to predict the thermodynamic conditions of gas hydrates - Jai Krishna Sahith Sayani; Niall J. English; Muhammad Saad Khan; Abulhassan Ali (Chemosphere, 2023)

Polyetherimide membrane with tunable porous morphology for safe lithium metal-based batteries - Arshad Hussain; Andleeb Mehmood; Adil Saleem; Muhammad K. Majeed; Waseem Raza; Rashid Iqbal; Sajid Rauf; Ali Saad; Yonggui Deng; Geng Luo; Kai Zong; Liu Wei; et al. (Chemical Engineering Journal, 2023)

Antidepressant activity of phytochemicals of Mangifera indica seeds assisted by integrated computational analysis - Uzma Saleem; Shafa Iman; Bashir Ahmad; Muhammad Ajmal Shah; Shabana Bibi; Mohammed Alqarni; Muhammad Saad Khan; Ghulam Mujtaba Shah; Haroon Khan; Reem Hasaballah Alhasani; Norah A. Althobaiti; Aishah E. Albalawi (Metabolic Brain Disease, 2023)

Inhibitory influence of amino acids on the formation kinetics of methane hydrates in oil-water and oil-brine systems - Abdulrab Abdulwahab Almashwali; Muhammad Saad Khan; Bhajan Lal; Quah Chong Jin; Khalik M. Sabil; Siak Foo Khor (Chemosphere, 2023)

Prediction of carbon-dioxide activity coefficient for solubility in ionic liquids using multi-non-linear regression analysis. - Sami-ullah Rather; Azmi M. Shariff; Aliyu Adebayo Sulaimon; Hisham S. Bamufleh; Ali Qasim; Muhammad Saad Khan; Hesham Alhumade; Usman Saeed; Walid M. Alalayah (Chemosphere, 2023)

Natural remedies for Alzheimer’s disease: A systematic review of randomized controlled trials - Saara Ahmad; Saad Bilal Ahmed; Asra Khan; Muhammad Wasim; Saiqa Tabassum; Saida Haider; Fatima Ahmed; Zehra Batool; Saima Khaliq; Hamna Rafiq; Prashant Tikmani; Anwar-ul-Hassan Gilani (Metabolic Brain Disease, 2023)

Trehalose: a promising osmo-protectant against salinity stress—physiological and molecular mechanisms and future prospective - Muhammad Nawaz; Muhammad Umair Hassan; Muhammad Umer Chattha; Athar Mahmood; Adnan Noor Shah; Mohamed Hashem; Saad Alamri; Maria Batool; Adnan Rasheed; Maryam A. Thabit; Haifa A. S. Alhaithloul; Sameer H. Qari (Molecular Biology Reports, 2022)

Evaluating the thermal-cooling induced effects on the Ambela granite properties (from Pakistan) using experimental and image processing techniques - Naseer Muhammad Khan; Liqiang Ma; Kewang Cao; Sajjad Hussain; Asghar Ali; Wei Liu; Saad S. Alarifi; Kausar Sultan shah; Sajid Khan; Yang Xiaoxu; Yujun Xu (Bulletin of Engineering Geology and the Environment, 2022)

Deep learning-based DOA estimation using CRNN for underwater acoustic arrays - Xiaoqiang Li; Jianfeng Chen; Jisheng Bai; Muhammad Saad Ayub; Dongzhe Zhang; Mou Wang; Qingli Yan (Frontiers in Marine Science, 2022)
In the marine environment, estimating the direction of arrival (DOA) is challenging because of the multipath signals and low signal-to-noise ratio (SNR). In this paper, we propose a convolutional recurrent neural network (CRNN)-based method for underwater DOA estimation using an acoustic array. The proposed CRNN takes the phase component of the short-time Fourier transform of the array signals as the input feature. The convolutional part of the CRNN extracts high-level features, while the recurrent component captures the temporal dependencies of the features. Moreover, we introduce a residual connection to further improve the performance of DOA estimation. We train the CRNN with multipath signals generated by the BELLHOP model and a uniform line array. Experimental results show that the proposed CRNN yields high-accuracy DOA estimation at different SNR levels, significantly outperforming existing methods. The proposed CRNN also exhibits a relatively short processing time for DOA estimation, extending its applicability.

Determinants of risk attitude and risk perception under changing climate among farmers in Punjab, Pakistan - Muhammad Farhan; Muhammad Asim Yasin; Khuda Bakhsh; Rafaqet Ali; Sami Ullah; Saad Munir (Natural Hazards, 2022)

Impact assessment of watercourse rehabilitation programs in Sindh, Pakistan using geospatial techniques - Arjumand Z. Zaidi; Sumaira Zafar; Muhammad Arslan; Saad Malik; Sana Ullah Shah; Asmat Ullah (Arabian Journal of Geosciences, 2022)

Fluid Flow Analysis of Integrated Porous Bone Scaffold and Cancellous Bone at Different Skeletal Sites: In Silico Study - Muhammad Azfar Noordin; Mohamad Ikhwan Kori; Abdul Hadi Abdul Wahab; Ardiyansyah Syahrom; Amir Putra Md Saad (Transport in Porous Media, 2022)

Estimation of some heavy metals contamination in waste newspapers - Hatem Abdel Moniem Ahmed; Ahmed Saad Gouhar; Muhammad Naeem Janjua; Nada Alhafez (Environmental Monitoring and Assessment, 2022)

Mediation of Growth and Metabolism of Pisum sativum in Salt Stress Potentially Be Credited to Thiamine - Rashda Naheed; Maryeum Zahid; Muhammad Aqeel; Muhammad Faisal Maqsood; Hina Kanwal; Noreen Khalid; Mohamed Hashem; Saad Alamri; Ali Noman (Journal of Soil Science and Plant Nutrition, 2022)

Investigating feasible sites for multi-purpose small dams in Swat District of Khyber Pakhtunkhwa Province, Pakistan: socioeconomic and environmental considerations - Anwar Hussain; Khalil Ur Rahman; Muhammad Shahid; Sajjad Haider; Quoc Bao Pham; Nguyen Thi Thuy Linh; Saad Shauket Sammen (Environment, Development and Sustainability, 2022)

Nutritional compositions, pathogenic microorganisms and heavy metal concentration in green turtle eggs (Chelonia mydas) from Terengganu and Sabah, Malaysia - Nor Hashikin Katni; Amirul Faiz Mohd Azmi; Maizah Mohd Abdullah; Mohd Uzair Rusli; Zunita Zakaria; Tengku Rinalfi Putra Tengku Azizan; Azlan Che’ Amat; Mohd Zamri Saad; Ina Salwany Md. Yasin; Muhammad Farhan Nazarudin; Hasliza Abu Hassim (Frontiers in Marine Science, 2022)
A total of 60 green turtle eggs were obtained from sampling sites in Terengganu and Sabah, Malaysia. Isolation and identification of bacteria from these eggs resulted in 12 genera of Gram-negative bacteria with 12 different species. The most frequently isolated bacteria were Salmonella (30.9%) and Proteus (23.7%). The rest of the microorganisms were Aeromonas, Escherichia, Citrobacter, Enterobacter, Klebsiella, Morganella, Pseudomonas, Shigella, Serratia and Photobacterium. A slight difference in total crude protein content was recorded in the samples from Terengganu and Sabah, at 16.3% Dry matter (DM) and 15.8% DM, respectively. Meanwhile, the crude fat content found in the samples from Terengganu was 9.88% DM and 7.79% DM from Sabah. In this study, α-linolenic acid, C18:3 n-3 (Terengganu: 16.87% DM) and linoleic acid, C18:2 n-6 (Sabah: 15.19% DM) were the most prevalent fatty acids in both samples. The green turtle egg samples from Terengganu showed higher value of total saturated fatty acid, total C18:3 n-3 and C18:2 n-6 and total polyunsaturated fatty acids as compared to green turtle eggs from Sabah. The results also revealed that majority of the essential amino acids (EAA) recorded in samples from both sampling sites was lysine (9.67% DM), with higher value recorded in green turtle egg from Terengganu. However, there were no significant differences ( p >0.05) in the nutritional compositions, fatty acid contents and amino acid compositions of the samples between the two sampling sites. Meanwhile, statistical analysis showed significant differences in heavy metal concentrations between the two sampling sites for all the six heavy metals detected in this study (Hg, Cd, Pb, Mn, Zn and Cu). The ranking of heavy metals concentration in turtle eggs from both sampling sites, in decreasing order is as follows: Zn > Cu > Mn > Pb > Cd > Hg. Overall, these results reveal the contents and contaminations of a green turtle egg, which may raise concern on public health risks. Findings from this study will also be beneficial for the future conservation of green turtle population when the consumption of their eggs should be stopped.

Targeting the TLR4/NF-κΒ Axis and NLRP1/3 Inflammasomes by Rosuvastatin: A Role in Impeding Ovariectomy-Induced Cognitive Decline Neuropathology in Rats - Muhammed A. Saad; Muhammad Y. Al-Shorbagy; Hany H. Arab (Molecular Neurobiology, 2022)

Repressors: the gatekeepers of phytohormone signaling cascades - Usman Aziz; Muhammad Saad Rehmani; Lei Wang; Baoshan Xian; Xiaofeng Luo; Kai Shu (Plant Cell Reports, 2022)

Hydrogen peroxide priming alleviates salinity induced toxic effect in maize by improving antioxidant defense system, ionic homeostasis, photosynthetic efficiency and hormonal crosstalk - Muhammad Umer Chattha; Muhammad Uzair Ul Hassan; Imran Khan; Muhammad Nawaz; Adnan Noor Shah; Abdul Sattar; Mohamed Hashem; Saad Alamri; Muhammad Talha Aslam; Haifa A. S. Alhaithloul; Muhammad Umair Hassan; Sameer H. Qari (Molecular Biology Reports, 2022)

Clean and sustainable transportation through electric vehicles — a user survey of three-wheeler vehicles in Pakistan - Mohammad Aamir Khan; Syed Fawad Bokhari; Aazir Khan; Muhammad Saad Amjad; Arooj Mobasher Butt; Muhammad Zeeshan Rafique (Environmental Science and Pollution Research, 2022)

Establishment of effective plantlets regeneration protocol via isolated microspore culture in Malaysian indica rice MR219 - Zuraida Abd Rahman; Zulkifli Ahmad Seman; Ayu Nazreena Othman; Mohamad Bahagia Ab Ghaffar; Shahril Ab Razak; Muhammad Fairuz Mohd Yusof; Khairun Hisam Nasir; Khairulmazmi Ahmad; Yeow Lit Chow; Teo Chee How; Norsharina Md Saad; Sreeramanan Subramaniam (Plant Biotechnology Reports, 2022)

Structural, Biochemical, and Physiological Adjustments for Toxicity Management, Accumulation, and Remediation of Cadmium in Wetland Ecosystems by Typha domingensis Pers - Noreen Akhter; Omey Habiba; Mehwish Hina; Muhammad Muslim Shahnaz; Fahad Mohammed Alzuaibr; Saad Alamri; Mohamed Hashem; Noreen Khalid; Muhammad Aqeel; Ali Noman (Water, Air, & Soil Pollution, 2022)

Anti-Huntington’s Effect of Butin in 3-Nitropropionic Acid-Treated Rats: Possible Mechanism of Action - Sultan Alshehri; Fahad A. Al-Abbasi; Mohammed M. Ghoneim; Syed Sarim Imam; Muhammad Afzal; Khalid Saad Alharbi; Muhammad Shahid Nadeem; Nadeem Sayyed; Imran Kazmi (Neurotoxicity Research, 2022)

A study on the synergetic effect of Bacillus amyloliquefaciens and dipotassium phosphate on Alternaria solani causing early blight disease of tomato - Muhammad Imran; Kamal A. M. Abo-Elyousr; Magdi A. A. Mousa; Maged M. Saad (European Journal of Plant Pathology, 2022)

Population structure and phylogenetic relationship of Peach [Prunus persica (L.) Batsch] and Nectarine [Prunus persica var. nucipersica (L.) C.K. Schneid.] based on retrotransposon markers - Hina Naeem; Faisal Saeed Awan; Peter Michael Dracatos; Muhammad Wasim Sajid; Shahzad Saleem; Qudsia Yousafi; Muhammad Saad Khan; Asim Mehmood; Bushra Zulfiqar (Genetic Resources and Crop Evolution, 2021)

Comparison of Early Succession and Scleractinian Recruitment Between Artificial Live Rocks and Terracotta Tiles - Yusof Muhammad Hamizan; Shahbudin Saad; Mohd Azrul Naim; Mohd Fikri Akmal Khodzori; Muhammad Faiz Mohd Hanapiah (Ocean Science Journal, 2021)

Understanding the neurological mechanism involved in enhanced memory recall task following binaural beat: a pilot study - Muhammad Danish Mujib; Muhammad Abul Hasan; Saad Ahmed Qazi; Aleksandra Vuckovic (Experimental Brain Research, 2021)
Binaural beat (BB) is a promising technique for memory improvement in elderly or people with neurological conditions. However, the related modulation of cortical networks followed by behavioral changes has not been investigated. The objective of this study is to establish a relationship between BB oscillatory brain activity evoked by stimulation and a behavioral response in a short term memory task. Three Groups A, B, and C of 20 participants each received alpha (10 Hz), beta (14 Hz), and gamma (30 Hz) BB, respectively, for 15 min. Their EEG was recorded in pre, during, and post BB states. Participants performed a digit span test before and after a BB session. A significant increase in the cognitive score was found only for Group A while a significant decrease in reaction time was noted for Groups A and C. Group A had a significant decrease of theta and increase of alpha power, and a significant increase of theta and decrease of gamma imaginary coherence (ICH) post BB. Group C had a significant increase in theta and gamma power accompanied by the increase of theta and gamma ICH post BB. The effectiveness of BB depends on the frequency of stimulation. A putative neural mechanism involves an increase in theta ICH in parieto-frontal and interhemispheric frontal networks.

Clostridium culturomicium sp. nov. and Clostridium jeddahitimonense sp. nov., novel members of the Clostridium genus isolated from the stool of an obese Saudi Arabian - Hoang Thong Kieu; Noémie Garrigou; Amael Fadlane; Ludivine Brechard; Nicholas Armstrong; Philippe Decloquement; Muhammad Yasir; Esam Ibraheem Azhar; Saad B. Al-Masaudi; Jean-Christophe Lagier; Maryam Tidjani Alou; Didier Raoult (Current Microbiology, 2021)

Geological and petrographic investigations of the Miocene Molasse deposits in Sub-Himalayas, District Sudhnati, Pakistan - Asim Javed; Ali Wahid; Muhammad Saleem Mughal; Muhammad Sabir Khan; Raja Saad Qammar; Syed Haroon Ali; Numair Ahmad Siddiqui; Muhammad Atif Iqbal (Arabian Journal of Geosciences, 2021)

Candidate Rlm6 resistance genes against Leptosphaeria. maculans identified through a genome-wide association study in Brassica juncea (L.) Czern - Hua Yang; Nur Shuhadah Mohd Saad; Muhammad Ishaq Ibrahim; Philipp E. Bayer; Ting Xiang Neik; Anita A. Severn-Ellis; Aneeta Pradhan; Soodeh Tirnaz; David Edwards; Jacqueline Batley (Theoretical and Applied Genetics, 2021)

Phyto-derivatives: an efficient eco-friendly way to manage Trogoderma granarium (Everts) (Coleoptera: Dermestidae) - Waqar Islam; Ali Noman; Komivi Senyo Akutse; Muhammad Qasim; Habib Ali; Ijaz Haider; Mohamed Hashem; Saad Alamri; Omar Mahmoud al Zoubi; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

Correction to: Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Physiological homeostasis for ecological success of Typha (Typha domingensis Pers.) populations in saline soils - Noreen Akhter; Muhammad Aqeel; Muhammad Muslim Shahnaz; Ghalia S. H. Alnusairi; Suliman Mohammed Alghanem; Abida Kousar; Mohamed Hashem; Hina Kanwal; Saad Alamri; Aisha Ilyas; Omar Mahmoud Al-zoubi; Ali Noman (Physiology and Molecular Biology of Plants, 2021)

Potential of Natural Bioactive Compounds in Management of Diabetes: Review of Preclinical and Clinical Evidence - Ameeduzzafar Zafar; Nabil K. Alruwaili; Dibya Sundar Panda; Syed Sarim Imam; Khalid Saad Alharbi; Muhammad Afzal; Khaled Shalaby; Imran Kazmi; Sultan Alshehri (Current Pharmacology Reports, 2021)

BBD-Based Development of Itraconazole Loaded Nanostructured Lipid Carrier for Topical Delivery: In Vitro Evaluation and Antimicrobial Assessment - Ameeduzzafar; Mohd Qumber; Nabil K Alruwaili; Syed Nasir Abbas Bukhari; Khalid Saad Alharbi; Syed Sarim Imam; Muhammad Afzal; Bader Alsuwayt; Ali Mujtaba; Asgar Ali (Journal of Pharmaceutical Innovation, 2021)

Correction to: In Silico Evaluation of Food Derived Bioactive Peptides as Inhibitors of Angiotensin Converting Enzyme (ACE) - Qudsia Yousafi; Jannat Batool; Muhammad Saad Khan; Tamsila Perveen; Muhammad Wasim Sajid; Abrar Hussain; Asim Mehmood; Shahzad Saleem (International Journal of Peptide Research and Therapeutics, 2021)

In Silico Evaluation of Food Derived Bioactive Peptides as Inhibitors of Angiotensin Converting Enzyme (ACE) - Qudsia Yousafi; Jannat Batool; Muhammad Saad Khan; Tamsila Perveen; Muhammad Wasim Sajid; Abrar Hussain; Asim Mehmood; Shahzad Saleem (International Journal of Peptide Research and Therapeutics, 2021)

Diversity of red palm weevil, Rhynchophorus ferrugineus Oliv. (Coleoptera: Curculionidae) in the Kingdom of Saudi Arabia: studies on the phenotypic and DNA barcodes - Sukirno Sukirno; Muhammad Tufail; Khawaja Ghulam Rasool; Mureed Husain; Abdulrahman Saad Aldawood (International Journal of Tropical Insect Science, 2020)

Scenario-based seismic hazard analysis using spectral element method in northeastern Pakistan - Saad Khan; Mark van der Meijde; Harald van der Werff; Muhammad Shafique (Natural Hazards, 2020)
Seismic hazard analysis is carried out in this study by estimating ground motion for hypothetical earthquakes in the area of Muzaffarabad, Pakistan, with the MT solution of the 2005 Kashmir earthquake. The earth’s topography influences seismic waves by scattering and reflecting it, thereby causing spatial variation in seismic response. Using the moment tensor solution of the 2005 Kashmir earthquake, we perform 25 spectral element method (SEM)-based 3D simulations along major faults in the study area. The SEM model incorporates the topography and homogeneous half-space characteristics. Our results show that, beside topography, the relative location of the source with respect to slopes also has an influence on the observed variation in ground shaking amplitudes. By integrating the mean and standard deviation of estimated ground shaking from 25 simulations, we present a seismic hazard map for the study area. The map summarizes the topographic and potential source location effect on seismic-induced ground shaking in the study area. It provides a classification from hazardous to safe in relative terms and can be used as a guide in earthquake preparedness.

Date palm rachis as a raw material for wood composite industry: anatomical characteristics - Pervaiz Rasheed Khan; Said Saad Hegazy; Muhammad Iqbal (Brazilian Journal of Botany, 2020)

The impacts of COVID-19 measures on global environment and fertility rate: double coincidence - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Xuan Hinh Voo; Abdelmohsen A. Nassani; Saad M. Alotaibi; Muhammad Moinuddin Qazi Abro; Khalid Zaman (Air Quality, Atmosphere & Health, 2020)

Formulation of Chitosan Polymeric Vesicles of Ciprofloxacin for Ocular Delivery: Box-Behnken Optimization, In Vitro Characterization, HET-CAM Irritation, and Antimicrobial Assessment - Ameeduzzafar; Nabil K Alruwaili; Syed Sarim Imam; Nasser Hadal Alotaibi; Nabil A. Alhakamy; Khalid Saad Alharbi; Sultan Alshehri; Muhammad Afzal; Sattam Khulaif Alenezi; Syed Nasir Abbas Bukhari (AAPS PharmSciTech, 2020)

TiO2 Coated-Asphalt Buton Photocatalyst for High-Performance Motor Vehicles Gas Emission Mitigation - Muhammad Zakir Muzakkar; Muhammad Nurdin; Ima Ismail; Maulidiyah Maulidiyah; Dwiprayogo Wibowo; Ratna Ratna; Siti Khatijah Md Saad; Akrajas Ali Umar (Emission Control Science and Technology, 2020)

ASTER-based remote sensing investigation of gypsum in the Kohat Plateau, north Pakistan - Asad Khan; Shah Faisal; Muhammad Shafique; Saad Khan; Alam Sher Bacha (Carbonates and Evaporites, 2020)

Core Competencies for Undergraduates in Bioengineering and Biomedical Engineering: Findings, Consequences, and Recommendations - John A. White; Donald P. Gaver; Robert J. Butera; Bernard Choi; Mary J. Dunlop; K. Jane Grande-Allen; Anna Grosberg; Robert W. Hitchcock; Aileen Y. Huang-Saad; Miiri Kotche; Aaron M. Kyle; Amy L. Lerner; et al. (Annals of Biomedical Engineering, 2020)

Photoperiodic stress induces genotype-specific shift in DNA methylation in Tartary buckwheat - Muhammad Saad; Helen Mary; Umar Amjid; Ghulam Shabir; Kashif Aslam; Shahid Masood Shah; Abdul Rehman Khan (Biologia Futura, 2019)
Tartary buckwheat, known for its rich source of health beneficial secondary metabolites, is cultivated in many areas of the world. Among different environmental factors, photoperiod strongly influence its growth, flowering time, and ultimately the yield. In this context, epigenetics could contribute significantly in the regulation of plant response against changing environment. Therefore, with the aim to study the involvement of DNA methylation in photoperiod mediated plant response, genome-wide DNA methylation analysis was performed in two accessions (A1 and A2) of Tartary buckwheat using three photoperiodic treatments, i.e., 10-hr light/day (T1), 12-hr light/day (T2), and 14-hr light/day (T3). Flowering time and plant fresh weight data revealed that accessions A1 and A2 prefer T1 and T2 treatments, respectively. Total DNA methylation ratio increased with the increase in photoperiod in accession A1 but decreased under same conditions in accession A2. Full methylation increased significantly while intensive decrease in hemimethylation was noted from T2 to T3 in A1, whereas full methylation strongly increased and hemimethylation strongly decreased from T1 to T2 in A2. Overall, the DNA methylation events appeared more frequently than demethylation events. This study reports for the first time an accession-/genotype specific pattern of shift in the DNA methylation under different photoperiodic treatments that will pave the way toward identification of specific genes involved in the regulation of plant response against photoperiodic stress.

Histo-morphological analysis of rice callus cultures reveals differential regeneration response with varying media combinations - Bushra Ijaz; Cristina Sudiro; Muhammad Zeeshan Hyder; Saad Imran Malik; Sumaira Farrakh; Fiorella Lo Schiavo; Tayyaba Yasmin (In Vitro Cellular & Developmental Biology - Plant, 2019)

Diversity and Abundance of Scleractinian Corals in the East Coast of Peninsular Malaysia: A Case Study of Redang and Tioman Islands - Khodzori Fikri Akmal; Saad Shahbudin; Mohd Hanapiah Muhammad Faiz; Yusof Muhammad Hamizan (Ocean Science Journal, 2019)

Environmental and economic impacts of better cotton: a panel data analysis - Sundas Zulfiquar; Muhammad Asim Yasin; Khuda Bakhsh; Rafaqet Ali; Samiullah; Saad Munir (Environmental Science and Pollution Research, 2019)

Sub-lethal effects of lufenuron exposure on spotted bollworm Earias vittella (Fab): key biological traits and detoxification enzymes activity - Muhammad Hafeez; Saad Jan; Muhammad Nawaz; Ehsan Ali; Bahar Ali; Muhammad Qasim; G. Mandela Fernández-Grandon; Muhammad Shahid; Mo Wang (Environmental Science and Pollution Research, 2019)

Characteristics of pipe corrosion scales in untreated water distribution system and effect on water quality in Peshawar, Pakistan - Dilawar Farhan Shams; Saeed Islam; Baoyou Shi; Waliullah Khan; Buddhika Gunawardana; Maryam Saad; Muhammad Qasim; Haider Ali Javed; Sahib Gul Afridi; Muhammad Naeem; Gul Shahzada Khan (Environmental Science and Pollution Research, 2019)

N-(2-hydroxyphenyl)acetamide and its gold nanoparticle conjugation prevent glycerol-induced acute kidney injury by attenuating inflammation and oxidative injury in mice - Rehan Ahmed Siddiqui; Shabana Usman Simjee; Nurul Kabir; Muhammad Ateeq; M. Raza Shah; Syed Saad Hussain (Molecular and Cellular Biochemistry, 2019)

Linear regression models for estimating true subsurface resistivity from apparent resistivity data - Sabiu Bala Muhammad; Rosli Saad (Journal of Earth System Science, 2018)

Prevalence of selected pharmaceuticals in surface water receiving untreated sewage in northwest Pakistan - Aisha Khan; Dilawar Farhan Shams; Waliullah Khan; Aamir Ijaz; Muhammad Qasim; Maryam Saad; Ayesha Hafeez; Shams Ali Baig; Nisar Ahmed (Environmental Monitoring and Assessment, 2018)

Exhaust emission profiling of fatty acid methyl esters and NOx control studies using selective synthetic and natural additives - Saad Afzal; Muhammad Waseem Mumtaz; Umer Rashid; Muhammad Danish; Muhammad Asam Raza; Ahtasham Raza; Hamid Mukhtar; Saud Ibrahim Al-Resayes (Clean Technologies and Environmental Policy, 2018)

Hutchinson–Gilford Progeria Syndrome: A Premature Aging Disease - Muhammad Saad Ahmed; Sana Ikram; Nousheen Bibi; Asif Mir (Molecular Neurobiology, 2017)

Effectiveness of carbon dioxide against different developmental stages of Cadra cautella and Tribolium castaneum - Mureed Husain; Sukirno Sukirno; Khalid Mehmood; Muhammad Tufail; Khawaja Ghulam Rasool; Waleed Saleh Alwaneen; Abdulrahman Saad Aldawood (Environmental Science and Pollution Research, 2017)

Synthesis and urease inhibitory activities of benzophenone semicarbazones/thiosemicarbazones - Arshia Arshia; Ajmal Khan; Khalid Mohammed Khan; Syed Muhammad Saad; Nida Iqbal Siddiqui; Sumaira Javaid; Shahnaz Perveen; M. Iqbal Choudhary (Medicinal Chemistry Research, 2016)

Assessment of seasonal variation for air pollutant accumulation by Zizyphus tree under washing treatment - Mohamed Abdulraheem Shaheen; Fathy Saad El-Nakhlawy; Fahd Mosallam Almehmadi; Muhammad Zahid Ihsan; Abdulmohsin Rajeh Al-Shareef (Environmental Monitoring and Assessment, 2016)

Osmoregulation and antioxidant production in maize under combined cadmium and arsenic stress - Shakeel Ahmad Anjum; Mohsin Tanveer; Saddam Hussain; Babar Shahzad; Umair Ashraf; Shah Fahad; Waseem Hassan; Saad Jan; Imran Khan; Muhammad Farrukh Saleem; Ali Ahsan Bajwa; Longchang Wang; et al. (Environmental Science and Pollution Research, 2016)

Development of MY-DRG casemix pharmacy service weights in UKM Medical Centre in Malaysia - Saad Ahmed Ali Jadoo; Syed Mohamed Aljunid; Amrizal Muhammad Nur; Zafar Ahmed; Dexter Van Dort (DARU Journal of Pharmaceutical Sciences, 2015)

Estimated daily intake and health risk of heavy metals by consumption of milk - Amir Ismail; Muhammad Riaz; Saeed Akhtar; Tariq Ismail; Zulfiqar Ahmad; Muhammad Saad Hashmi (Food Additives & Contaminants Part B-Surveillance, 2015)

Direct detection of saponins in crude extracts of soapnuts by FTIR - Meshari Saad Almutairi; Muhammad Ali (Natural Product Research, 2015)

Synthesis of phenyl thiazole hydrazones and their activity against glycation of proteins - Khalid Mohammed Khan; Muhammad Irfan; Mahwish Ashraf; Muhammad Taha; Syed Muhammad Saad; Shahnaz Perveen; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)